Potensi Pengembangan Wilayah di Kabupaten Gayo Lues Provinsi Aceh - Ikhwan Alfiansyah; Irianto Nasution (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
This study aims to analyze the potential of Gayo Lues Regency, Aceh Province. This study uses secondary data in the time series, namely the GRDP of Gayo Lues Regency, according to business fields in 2018 – 2022. Analysis tools used with Location Quotient (LQ) methods, Shift share analysis (SSA), and Klassen Typology. The results of the three analyses, Location Analysis of quotient results (LQ), SSA, and Klassen Typology, show that sectors that are leading sectors with criteria classified as base, prospective, superior, and developed sectors are the agriculture, forestry, and fisheries sector, government administration sector and health services sector and social activities. Although these three sectors are the mainstay, they are classified as depressed growth sectors.